2011
DOI: 10.1638/2010-0209.1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatozoonssp. (Apicomplexa: Hepatozoidae) Infection and Selected Hematological Values of the Neotropical Rattlesnake,Crotalus durissus collilineatus(Linnaeus, 1758) (Serpentes: Viperidae), from Brazil

Abstract: This study aims to establish the hematological values of Crotalus durissus collilineatus snakes captured in Brazil as well as to verify the effects of hematozoan infection on these snakes. Eighty-three blood samples were drawn from C. d. collilineatus specimens for analysis. The sample set was composed of 30 males and 30 females, recently caught from the wild, and 11 males and 12 females bred in captivity. Blood samples were used to determine red blood cell counts, white blood cell counts, thrombocyte counts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…However, the effect of such infections on leukocyte profiles is poorly known. Several studies on hematozoan infection in reptiles and amphibians have shown either changes in leukocyte densities or reductions in humoral components of the immune response when infected (Ujvari and Madsen, 2005;Bonadiman et al, 2010;Motta et al, 2011;Shutler and Marcogliese, 2011;McFarland et al, 2012). Although many hematozoan parasites are considered nonpathogenic (Brown et al, 2006;Jacobson, 2007;Stacy et al, 2011), some do result in a variety of physiological, reproductive, and behavioral changes (Schall, 2002;Ujvari et al, 2004;Amo et al, 2005;Ujvari and Madsen, 2005;Vardo-Zalik and Schall, 2008;Motta et al, 2011), and further examination of leukocyte alterations or other immune responses to these infections should clarify this parasite-host biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of such infections on leukocyte profiles is poorly known. Several studies on hematozoan infection in reptiles and amphibians have shown either changes in leukocyte densities or reductions in humoral components of the immune response when infected (Ujvari and Madsen, 2005;Bonadiman et al, 2010;Motta et al, 2011;Shutler and Marcogliese, 2011;McFarland et al, 2012). Although many hematozoan parasites are considered nonpathogenic (Brown et al, 2006;Jacobson, 2007;Stacy et al, 2011), some do result in a variety of physiological, reproductive, and behavioral changes (Schall, 2002;Ujvari et al, 2004;Amo et al, 2005;Ujvari and Madsen, 2005;Vardo-Zalik and Schall, 2008;Motta et al, 2011), and further examination of leukocyte alterations or other immune responses to these infections should clarify this parasite-host biology.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly of interest is any change in the leukocyte population because such changes indicate an immune response initiated by the reptilian host (Bonadiman et al, 2010). Although many hematozoan infections are considered nonpathogenic for their reptilian hosts (Brown et al, 2006;Jacobson, 2007;Sperry et al, 2009;Stacy et al, 2011;Xuereb et al, 2012), some parasites do cause a variety of negative effects, including reduced fecundity, anemia, and reduced weight (Schall, 2002;Ujvari et al, 2004;Amo et al, 2005;Ujvari and Madsen, 2005;Vardo-Zalik and Schall, 2008;Motta et al, 2011). Changes in the leukocyte patterns can greatly affect the overall pathology caused by the parasite, may influence the parasite's infection dynamics in its host, and may predispose an animal to other infectious organisms.…”
mentioning
confidence: 99%
“…terrificus (Santos et al, 2008) e C.d. collilineatus (Motta et al, 2011) e também em outras espécies como Bothrops leucurus (Grego et al, 2006), Ophiophagus hannah (Salakij et al, 2002) e Natrix natrix natrix (Wojtaszek, 1991), mostrando que os nossos exemplares estavam saudáveis, corroborando com os exames físicos dos animais, sem evidências de sintomatologia clínica.…”
Section: Discussionunclassified